2013
DOI: 10.1136/heartjnl-2012-303325
|View full text |Cite
|
Sign up to set email alerts
|

Heart-type fatty acid-binding protein in the early diagnosis of acute myocardial infarction

Abstract: hFABP and copeptin do not improve the diagnosis of patients with chest pain without ST-segment elevation, but may be useful for risk stratification beyond hs-TnT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 34 publications
2
62
0
Order By: Relevance
“…Consequently, eight studies (Table 1) were included for quantitative analysis. [15][16][17][18][19][20][21][22] Overall, 3395 patients were included in the final analysis. Among these, 716 patients (21.1%) were eventually diagnosed with AMI according to the Universal Definition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, eight studies (Table 1) were included for quantitative analysis. [15][16][17][18][19][20][21][22] Overall, 3395 patients were included in the final analysis. Among these, 716 patients (21.1%) were eventually diagnosed with AMI according to the Universal Definition.…”
Section: Resultsmentioning
confidence: 99%
“…18 Four studies had a prospective design, 15,[20][21][22] while the rest performed retrospective analyses of frozen plasma samples. Three studies used hsTnI, 19,20,22 four used hsTnT 15,16,21 and one assayed both. 17 The analyser for hsTnT was produced by Roche Diagnostics in all (99% cut-off 14 ng/L), while hsTnI was measured using the Beckman-Coulter AccuTnI Enhanced (cut-off 40 ng/L) in one study, 17 Siemens TnI-Ultra assay (99% cut-off 40 ng/L) in two, 17,22 and the Abbott-Architect assay (99% cut-off: 28 and 32 ng/ L, respectively) in the remainder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study in 343 patients using both a contemporary and a sensitive cTnI assay showed a significant increase in the AUCs for the combination with H-FABP with the contemporary (Centaur, cTnI Siemens) assay but not with the highly sensitive assay (TnI-Ultra, Siemens). 22 Similarly, Reiter et al 23 showed no added diagnostic value for H-FABP on top of hs-cTnT measurements. On the other hand, Keller et al 3 showed a combined sensitivity of 85% compared to 73% for hs-cTnI (Architect STAT High sensitive troponin, Abbott Diagnostics) alone.…”
Section: Discussionmentioning
confidence: 99%